2011
DOI: 10.1007/s11409-011-9070-z
|View full text |Cite
|
Sign up to set email alerts
|

Measuring strategy use in context with multiple-choice items

Abstract: A number of authors have presented data that challenge the validity of self-report of strategy use or choice of strategy. We created a multiple-choice measure of students' strategy use based on the work of Kozminsky, E., and Kozminsky, L. (2001), and tested it with three samples as part of a series of studies testing the fit of the DIME model of reading comprehension. One study was conducted at the high school level (N=175) and two at the undergraduate level (N=185 and 737). Over the three studies with three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 32 publications
(27 reference statements)
1
10
0
3
Order By: Relevance
“…Within the regression models, content knowledge significantly predicted strategy knowledge across grade levels. This finding supports the results of a study conducted by Cromley and Azevedo (2011), who found that the application of domain-specific strategies is determined by students' background knowledge. Also, the findings of H. Kim and Pedersen (2011) can be supported.…”
Section: Effects Of Covariates On Strategy Knowledgesupporting
confidence: 90%
“…Within the regression models, content knowledge significantly predicted strategy knowledge across grade levels. This finding supports the results of a study conducted by Cromley and Azevedo (2011), who found that the application of domain-specific strategies is determined by students' background knowledge. Also, the findings of H. Kim and Pedersen (2011) can be supported.…”
Section: Effects Of Covariates On Strategy Knowledgesupporting
confidence: 90%
“…As Efklides (2014) proposes, it is important to examine the various cognitive, affective and motivational strategies that students apply for regulating their learning in various learning domains. For example, students' knowledge, perceptions of the task-difficulty, perceptions of self-efficacy might influence performance expectations and performance, as literature suggests (e.g., Benbenutty et al, 2014;Cera et al, 2013;Cromley & Azevedo, 2011;Schunk & Zimmerman, 2006;Smit et al, 2017;Stephanou, 2008). The Jr. MAI might be another influential factor of these findings, as the extent of correlations between metacognition and academic indicators depends considerably on how metacognition is assessed, with favoring the content-task specific method (Tobias & Everson, 2009;Young & Fry, 2008).…”
Section: The Role Of Metacognition and Self-regulatory Learning Stylementioning
confidence: 99%
“…Most, of the previous researches examining the inter-correlations or inter-effects of the above concepts have focused on mathematics or/and language, while other school subjects have almost ignored, although features of the task affect learners' beliefs and, subsequent application, about skills and strategies are required, and competence and control beliefs (see Cromley & Azevedo, 2011;Efklides, 2014;Kurman, 2001;Ommundsen, Haugen, & Lund, 2005;Pressley & Gaskins, 2006;Schunk & Zimmerman, 2006;Wang & Holcombe, 2010). This study focuses on language, mathematics and physical education.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, students can differ in their frame of reference as to which situations they have in mind when answering the questions and interpreting the scales (McNamara 2011;Schellings 2011). Thirdly, the way students answer self-report questionnaires may be biased by triggers in the questions which prompt them to wrongly label their own behavior or by social desirability (Cromley and Azevedo 2011;Veenman 2011a). Therefore, students are typically quite inaccurate in reporting their own metacognitive behavior.…”
Section: Theoretical Frameworkmentioning
confidence: 99%